THE EXPRESSION OF THREAT IN JIHADIST PROPAGANDA - Ascone, Laura; Longhi, Julien (Fragmentum, 2018)
This study investigates the expression of threat in jihadist propaganda from a semantico-pragmatic perspective. The analysis was conducted on the two official online magazines published by Daesh: the English Dabiq, and the French Dar al-Islam. Since the two magazines address two different readerships, it was hypothesised that differences in the way threat is expressed would be identified. The combination of both qualitative and quantitative approaches has allowed us to examine quantitative results in a more detailed way and, therefore, to obtain more solid results. This study revealed that the two magazines differ in the way threat is verbalised.